Propylene-based resin composition and its uses

JP7645097B2Active Publication Date: 2025-03-13PRIME POLYMER CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021034653
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-04
Publication Date
2025-03-13
Estimated Expiration
2041-03-04

AI Technical Summary

Benefits of technology

【0012】 本発明のプロピレン系樹脂組成物から得られる成形体は、リブ近傍での成形収縮により生じる応力が起因となって発生する白化(ヒケ白化)が抑制され、且つ、剛性、耐衝撃性のバランスに優れた成形体である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645097000002
    Figure 0007645097000002
  • Figure 0007645097000001
    Figure 0007645097000001
Patent Text Reader

Abstract

To provide a propylene-based resin composition from which a molding that suppresses sink whitening in the vicinity of a rib and has an excellent balance between rigidity and impact resistance can be obtained, and a large-sized molding.SOLUTION: A composition contains 85-95 pts.mass of a propylene-based polymer A satisfying the following A1 to A5, and 5-15 parts of an ethylene-α-olefin copolymer B satisfying the following B1 and B2. A1) MFRA measured at a measurement temperature of 230°C and a load of 2.16 kg according to JIS K 7210 of 1-30 g / 10 minutes. A2) Containing a propylene homopolymer segment and a propylene-ethylene copolymer segment. A3) Containing 86-95 mass% of an insoluble part (Dinsol), and 5-14 mass% of a soluble part (Dsol) in room temperature n-decane. A4) Content of a constitutional unit derived from ethylene of the Dsol of 25-45 mass%. A5) Intrinsic viscosity [η] in 135°C decalin of the Dsol of 2.5-4.0dL / g. B1) MFRB at a measurement temperature of 190°C of 1-30 g / 10 minutes. B2) Density of 950-966 kg / m3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a propylene resin composition suitable for obtaining a molded article having an excellent balance between rigidity and impact resistance and suppressed whitening due to molding shrinkage. [Background technology]

[0002] Polyolefins (olefin polymers) such as polyethylene and polypropylene require little energy to produce, are lightweight and highly recyclable, and as such are attracting increasing attention in various industrial sectors as they work towards the 3Rs (Reduce, Reuse, Recycle) to create a recycling-oriented society. Polyolefins are used in a variety of fields, including daily necessities, kitchen utensils, packaging films, home appliances, machine parts, electrical parts, and automobile parts.

[0003] Among olefin polymers, polypropylene is excellent in rigidity and heat resistance, but is inferior to polyethylene in cold resistance and impact resistance. Therefore, many methods have been proposed for improving the cold resistance and impact resistance of polypropylene.

[0004] For example, Patent Document 1 describes a method for producing a polypropylene using an ethylene-propylene block copolymer having a melt flow rate of 2 to 80 g / 10 min at 230° C., a homo part stereoregularity of 0.960 or more, and a total ethylene content of 2 to 12% by weight, and a polymerizable composition comprising 60 to 99 parts by weight of the block copolymer and a polymerizable composition having a melt flow rate of 1 to 60 g / 10 min at 190° C. and a density of 0.860 to 0.940 g / cm. 3 It has been shown that mixing with 1 to 40 parts by weight of polyethylene improves the impact resistance of small molded products such as caps in the food and medical fields and reduces whitening that occurs when dropped.

[0005] Patent Document 2 also describes a method for producing a polypropylene using an ethylene-propylene block copolymer having a melt flow rate of 2 to 20 (g / 10 min) at 230°C, a homo-part stereoregularity of 0.960 or more, and a total ethylene content of 6 to 12 (wt%), and mixing 85 to 95 parts by weight of the block copolymer with a polymerizable composition having a melt flow rate of 30 to 60 (g / 10 min) at 190°C and a density of 0.957 to 0.966 (g / cm 3 It has been shown that mixing the resin with 5 to 15 parts by weight of high density polyethylene (PE) improves the impact resistance of small molded articles such as beverage caps.

[0006] On the other hand, large molded articles such as containers and pallets are often molded articles with ribs because their intended use requires high levels of physical strength, such as rigidity and impact resistance. However, it has been found that molded articles with ribs can sometimes be partially whitened due to stress caused by shrinkage of the molded article during molding. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-255319 A [Patent Document 2] JP 2004-182955 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a propylene-based resin composition suitable for obtaining a molded article that is suppressed from whitening (sink mark whitening) caused by stress generated by molding shrinkage near a rib and has an excellent balance between rigidity and impact resistance, and to provide a large molded article, such as a container or a pallet, made of the composition.

[0009] Another object of the present invention is to provide a propylene-based resin composition that can suppress sink mark whitening and achieve the target balance between rigidity and impact resistance required for large molded articles such as containers and pallets, by optimizing the composition of the propylene-based resin composition and the ethylene-based polymer component to be blended.

[0010] Another object of the present invention is to provide large molded articles such as containers and pallets using this propylene-based resin composition. [Means for solving the problem]

[0011] The present invention relates to a propylene-based resin composition comprising 85 to 95 parts by mass of a propylene-based polymer (A) satisfying the following requirements (A1) to (A5), and 5 to 15 parts by mass of an ethylene-based polymer (B) satisfying the following requirements (B1) and (B2) (wherein the total amount of the propylene-based polymer (A) and the ethylene-based polymer (B) is 100 parts by mass). (A1) Melt flow rate (MFR) measured at 230°C and a load of 2.16 kg in accordance with JIS K 7210 A ) is 1 to 30g / 10min. (A2) Contains a propylene homopolymer segment obtained by polymerizing propylene alone, and a propylene-ethylene copolymer segment obtained by copolymerizing propylene and ethylene. (A3) The part that is insoluble in n-decane at room temperature (D insol ) at 86 to 95 mass%, and the portion soluble in n-decane at room temperature (D sol ) from 5 to 14 mass% [wherein (D insol ) and (D sol ) is taken as 100 mass %. (A4) The part soluble in n-decane at room temperature (D sol ) has a content of structural units derived from ethylene of 25% by mass or more and less than 45% by mass. (A5) The part soluble in n-decane at room temperature (D sol ) has an intrinsic viscosity [η] of 2.5 to 4.0 dL / g in decalin at 135°C. (B1) Melt flow rate (MFR) measured at a temperature of 190°C and a load of 2.16 kg in accordance with JIS K 7210 B ) is greater than 1g / 10min and less than 30g / 10min. (B2) Density is 950-966kg / m 3 It is. Effect of the Invention

[0012] The molded article obtained from the propylene-based resin composition of the present invention is a molded article in which whitening (sink mark whitening) caused by stress generated by molding shrinkage in the vicinity of ribs is suppressed, and the molded article has an excellent balance between rigidity and impact resistance. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a plan view and a side view of the molded article used in the examples and the reference example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Propylene-based polymer (A)> The propylene polymer (A), which is one of the components constituting the propylene resin composition of the present invention, is a propylene polymer that satisfies the following requirements (A1) to (A5).

[0015] [Requirement (A1)] The melt flow rate (MFR) was measured at 230°C and a load of 2.16 kg in accordance with JIS K 7210. A ) is 1 to 30 g / 10 min, preferably 1 to 20 g / 10 min, and more preferably 1 to 15 g / 10 min. MFR A If the MFR is below the above range, there is a risk of short shots occurring when the propylene-based resin composition is injection molded. A If the content exceeds the above range, the mechanical strength of a molded article obtained from the propylene-based resin composition may decrease.

[0016] [Requirements (A2)] It contains a propylene homopolymer segment obtained by polymerizing propylene alone, and a propylene-ethylene copolymer segment obtained by copolymerizing propylene and ethylene. The propylene polymer (A) according to the present invention contains a propylene homopolymer segment and a propylene-ethylene copolymer segment, and therefore a molded article obtained from the propylene resin composition has an excellent balance between rigidity and impact resistance required for a large molded article.

[0017] [Requirements (A3)] The part that is insoluble in n-decane at room temperature (D insol ) is 86 to 95 mass%, preferably 86 to 92 mass%, more preferably 86 to 90 mass%, and a portion soluble in n-decane at room temperature (D sol ) in an amount of 5 to 14 mass%, preferably 8 to 14 mass%, more preferably 10 to 14 mass% [wherein (D insol ) and (D sol ) is taken as 100 mass %.

[0018] In the propylene polymer (A), the portion insoluble in n-decane (D insol ) is usually a component that is mainly composed of structural units derived from propylene, has crystallinity, and is thought to exhibit high rigidity. The n-decane soluble portion (D sol ) is a component that is usually composed mainly of structural units derived from propylene and ethylene. sol The component exhibits no or low crystallinity, and is considered to have a low glass transition temperature, impact resistance, and compatibility with the ethylene-α-olefin copolymer (B). This is sometimes called the rubber component. The propylene polymer (A) usually has a portion that is insoluble in n-decane (D insol ) and the n-decane soluble portion (D sol ) is a propylene-based copolymer (so-called block copolymer).

[0019] D sol The proportion of is below the above range, and D insolIf the ratio of exceeds the above range, the impact resistance of the molded article obtained from the propylene-based resin composition tends to decrease, and the effect of improving sink mark whitening tends to be inferior. sol It is believed that the decrease in the proportion of reduces the absorbed energy against impact and reduces the effect of dispersing and absorbing the stress generated during molding shrinkage.

[0020] On the other hand, D insol The proportion of is below the above range, and D sol If the ratio of exceeds the above range, the moldability at high speed of the propylene-based resin composition may be deteriorated, and the rigidity of the molded article obtained from the propylene-based resin composition tends to decrease. This is because the ratio of D insol This is thought to be due to a decrease in the component D insol The ratio of D sol The ratio is measured by the method employed in the examples described later.

[0021] [Requirements (A4)] The part soluble in n-decane at room temperature (D sol The content of structural units derived from ethylene in D is 25% by mass or more and less than 45% by mass, preferably 27 to 43% by mass, and more preferably 30 to 40% by mass. sol The total amount of the structural units derived from ethylene and the structural units derived from propylene is taken as 100 mass %. The part soluble in n-decane at room temperature (D sol The content of ethylene-derived structural units in the propylene homopolymer segment contributes to the compatibility of the propylene-ethylene copolymer segment with the propylene homopolymer segment.

[0022] If the content of the structural units derived from ethylene is below the above range, the rigidity of the molded article obtained from the propylene-based resin composition tends to be inferior. This is believed to be because the compatibility of the propylene homopolymer segment and the propylene-ethylene copolymer segment becomes high, and the propylene homopolymer segment that contributes to the rigidity is dissolved in the propylene-ethylene copolymer segment, resulting in a decrease in crystallinity. On the other hand, if the content of the structural units derived from ethylene is above the above range, the molded article obtained from the propylene-based resin composition tends to be prone to the generation of bumps, and to the occurrence of a decrease in impact resistance and a defective appearance. This is believed to be because the compatibility of the propylene homopolymer segment and the propylene-ethylene copolymer segment becomes low, resulting in poor dispersion.

[0023] [Requirements (A5)] The part soluble in n-decane at room temperature (D sol ) in decalin at 135℃ [η sol ] is 2.5 to 4.0 dL / g, preferably 2.7 to 3.8 dL / g, and more preferably 2.9 to 3.6 dL / g. The intrinsic viscosity [η sol The values ​​of [ ] are those measured by the method employed in the examples described later.

[0024] Intrinsic viscosity [η sol If the ratio of the propylene-based resin composition to the total weight of the resin is less than the above range, the impact resistance of the molded article obtained from the propylene-based resin composition tends to be poor. sol This is thought to be because the molecular weight of the polymer decreases, and the impact absorption energy decreases. sol If the ratio of the propylene-based resin composition to the total weight of the resin exceeds the above range, the molded product obtained from the propylene-based resin composition is likely to have small bumps, and the impact resistance is likely to be reduced and the appearance is likely to be poor. sol This is believed to be because the molecular weight of the polymer is high, causing poor dispersion.

[0025] The propylene polymer (A) according to the present invention is not particularly limited in its production method, but is usually obtained by copolymerizing propylene and ethylene in the presence of a metallocene compound-containing catalyst or a Ziegler-Natta catalyst.

[0026] The propylene polymer (A) according to the present invention is preferably obtained by copolymerizing propylene and ethylene in the presence of a Ziegler-Natta catalyst, since this makes it easier to obtain a resin having a broad molecular weight distribution and good moldability.

[0027] (Catalyst containing metallocene compound) The metallocene compound-containing catalyst may be a metallocene catalyst consisting of at least one compound selected from a metallocene compound, an organometallic compound, an organoaluminum oxy compound, and a compound capable of reacting with the metallocene compound to form an ion pair, and further comprising a particulate carrier as required. A preferred example is a metallocene catalyst capable of stereoregular polymerization such as an isotactic or syndiotactic structure. Among the metallocene compounds, preferred are the crosslinked metallocene compounds exemplified in International Publication No. 01 / 27124 and the metallocene compounds described in

[0068] to

[0076] of International Publication No. 2010 / 74001. In addition, the compounds that react with the organometallic compound, the organoaluminum oxy compound, and the transition metal compound to form an ion pair, and further comprising a particulate carrier as required, may be compounds disclosed in International Publication No. 01 / 27124, JP-A-11-315109, and the like, without any restrictions.

[0028] (Ziegler-Natta catalyst) The propylene-based polymer (A) can be produced by using a highly stereoregular Ziegler-Natta catalyst. Various known catalysts can be used as the highly stereoregular Ziegler-Natta catalyst. For example, a catalyst can be used that is composed of (a) a solid titanium catalyst component that contains magnesium, titanium, a halogen, and an electron donor, (b) an organometallic compound catalyst component, and (c) an organosilicon compound catalyst component that has at least one group selected from the group consisting of a cyclopentyl group, a cyclopentenyl group, a cyclopentadienyl group, and derivatives thereof, and this catalyst component can be produced by a known method, for example, the method described in

[0078] to

[0094] of International Publication No. 2010 / 74001.

[0029] When propylene is polymerized using a catalyst comprising the above-mentioned solid titanium catalyst component (a), organometallic compound catalyst component (b), and organosilicon compound catalyst component (c), a prepolymerization can be carried out in advance. In the prepolymerization, olefins are polymerized in the presence of the solid titanium catalyst component (a), the organometallic compound catalyst component (b), and, if necessary, the organosilicon compound catalyst component (c).

[0030] As the olefin to be prepolymerized, an α-olefin having 2 to 8 carbon atoms can be used. Specifically, linear olefins such as ethylene, propylene, 1-butene, and 1-octene; olefins having a branched structure such as 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene can be used. These may be copolymerized.

[0031] The prepolymerization is desirably carried out so that about 0.1 to 1000 g, preferably about 0.3 to 500 g of polymer is produced per 1 g of the solid titanium catalyst component (a). If the amount of prepolymerization is too large, the efficiency of production of the (co)polymer in the main polymerization may decrease. In the prepolymerization, the catalyst can be used at a concentration considerably higher than the catalyst concentration in the system in the main polymerization.

[0032] In the main polymerization, it is desirable to use the solid titanium catalyst component (a) (or prepolymerization catalyst) in an amount of about 0.0001 to 50 millimoles, preferably about 0.001 to 10 millimoles, calculated as titanium atoms per 1 L of polymerization volume. It is desirable to use the organometallic compound catalyst component (b) in an amount of about 1 to 2000 moles, preferably about 2 to 500 moles, calculated as metal atoms, per mole of titanium atoms in the polymerization system. It is desirable to use the organosilicon compound catalyst component (c) in an amount of about 0.001 to 50 moles, preferably about 0.01 to 20 moles, per mole of metal atoms of the organometallic compound catalyst component (b).

[0033] <Method for producing propylene polymer (A)> The propylene polymer (A) can be obtained by copolymerizing propylene and ethylene in the presence of the above-mentioned metallocene compound-containing catalyst or Ziegler-Natta catalyst.

[0034] When the propylene polymer (A) is produced by continuous multi-stage polymerization, propylene is homopolymerized or propylene and ethylene are copolymerized in each stage. The polymerization may be carried out by any of gas phase polymerization method or liquid phase polymerization method such as solution polymerization method or suspension polymerization method, and each stage may be carried out by a different method. The polymerization may be carried out by any of continuous and semi-continuous methods, and each stage may be carried out by dividing it into a plurality of polymerization vessels, for example, 2 to 10 polymerization vessels. From an industrial perspective, polymerization by a continuous method is most preferable, and in this case, it is preferable to divide the second and subsequent stages of polymerization into two or more polymerization vessels, which can suppress the generation of gel.

[0035] As the polymerization medium, an inert hydrocarbon may be used, or liquid propylene may be used. The polymerization conditions for each stage are appropriately selected such that the polymerization temperature is within the range of about -50 to +200°C, preferably about 20 to 100°C, and the polymerization pressure is within the range of normal pressure to 10 MPa (gauge pressure), preferably about 0.2 to 5 MPa (gauge pressure).

[0036] The propylene polymer (A) can be obtained, for example, by continuously carrying out the following two steps ([step 1] and [step 2]) in a reactor in which two or more polymerization vessels are connected in series. When producing the propylene polymer (A), [step 1] may be carried out in each of the polymerization vessels in which two or more reactors are connected in series, or [step 2] may be carried out in each of the polymerization vessels in which two or more reactors are connected in series. Alternatively, [step 1] and [step 2] may be carried out separately, and the polymers obtained in each step may be melt-kneaded using a single-screw extruder, a multi-screw extruder, a kneader, a Banbury mixer, or the like to produce the propylene polymer (A).

[0037] Hereinafter, a method for producing the propylene polymer (A) by continuously carrying out [Step 1] and [Step 2] will be described.

[0038] [Step 1] is a step of polymerizing propylene at a polymerization temperature of 0 to 100°C and a polymerization pressure of normal pressure to 5 MPa gauge pressure, insol This is a process for producing a propylene-based polymer, which is the main component of the process. In order to obtain a molded product with excellent rigidity, it is preferable to polymerize only propylene. In addition, a chain transfer agent, typically hydrogen gas, is also introduced as necessary to control the intrinsic viscosity [η insol ] may be adjusted.

[0039] In addition to the above method, the melt flow rate (MFR) (JIS K 7210, measurement temperature 230°C, load 2.16 kg) can be adjusted by melt-kneading the propylene polymer obtained by polymerization in the presence of an organic peroxide. The MFR can be increased by melt-kneading the propylene polymer obtained by polymerization in the presence of an organic peroxide, and the MFR can be further increased by increasing the amount of organic peroxide added when melt-kneading in the presence of an organic peroxide. When the propylene polymer obtained by polymerization is melt-kneaded in the presence of an organic peroxide, it is preferable to use 0.005 to 0.05 parts by mass of the organic peroxide per 100 parts by mass of the propylene polymer. The melt-kneading in the presence of the organic peroxide may be performed after the following post-treatment process.

[0040] The organic peroxide that can be used in the melt kneading treatment in the presence of the organic peroxide is not particularly limited, but examples thereof include benzoyl peroxide, t-butyl perbenzoate, t-butyl peracetate, t-butylperoxyisopropyl carbonate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexyne-3, t-butyl-diperadipate, t-butylperoxy-3,5,5-trimethylhexanoate, methyl-ethyl ketone peroxide, cyclohexanone peroxide, di-t-butyl peroxide, diquimyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl- Examples of organic peroxides include 2,5-di-(t-butylperoxy)hexyne-3, 1,3-bis-(t-butylperoxyisopropyl)benzene, t-butylkiyumyl peroxide, 1,1-bis-(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis-(t-butylperoxy)cyclohexane, 2,2-bis-(t-butylperoxy)butane, p-menthane hydroperoxide, di-isopropylbenzene hydroperoxide, kiyumene hydroperoxide, t-butyl hydroperoxide, p-cymene hydroperoxide, 1,1,3,3-tetra-methylbutyl hydroperoxide, and 2,5-di-methyl-2,5-di-(hydroperoxy)hexane. Among these, 2,5-di-methyl-2,5-di-(benzoylperoxy)hexane and 1,3-bis-(t-butylperoxyisopropyl)benzene are more preferred.

[0041] [Step 2] is a step of copolymerizing propylene and ethylene at a polymerization temperature of 0 to 100°C and a polymerization pressure of normal pressure to 5 MPa gauge pressure, and by increasing the ratio of the amount of ethylene fed to the amount of propylene fed in [Step 1], D sol This is the process for producing propylene-ethylene copolymer (elastomer), which is the main component of the polymer. If necessary, a chain transfer agent such as hydrogen gas is also introduced to control the intrinsic viscosity [ηsol ] may be adjusted.

[0042] [Step 1] is a step of polymerizing propylene at a polymerization temperature of 0 to 100°C and a polymerization pressure of normal pressure to 5 MPa gauge pressure, insol This is the process for producing propylene homopolymer, which is the main component of the copolymer. If necessary, a chain transfer agent such as hydrogen gas is also introduced to control the intrinsic viscosity [η insol ] may be adjusted.

[0043] In addition to the above method, the propylene polymer obtained by polymerization can be melt-kneaded in the presence of an organic peroxide to obtain an MFR. A The propylene polymer obtained by polymerization is melt-kneaded in the presence of an organic peroxide to adjust the MFR. A The MFR is increased by increasing the amount of organic peroxide added during melt kneading treatment in the presence of organic peroxide. A becomes higher. When the propylene-based polymer obtained by polymerization is melt-kneaded in the presence of an organic peroxide, it is preferable to use 0.005 to 0.05 parts by mass of the organic peroxide per 100 parts by mass of the propylene-based polymer. The melt-kneading in the presence of the organic peroxide may be carried out after the post-treatment step described below. The organic peroxide is not particularly limited, and examples thereof include conventionally known organic peroxides such as 2,5-di-methyl-2,5-di-(benzoylperoxy)hexane and 1,3-bis-(t-butylperoxyisopropyl)benzene.

[0044] The above D in requirement (A3) insol The ratio of D sol The ratio of D can be adjusted by adjusting the polymerization times of the above [Step 1] and [Step 2]. In other words, by increasing the ratio of the polymerization time of [Step 1] to the total polymerization time, insol Increase the proportion of D sol In addition, by increasing the ratio of the polymerization time in [Step 2] to the total polymerization time, the ratio of D insol Decrease the proportion of D solThe proportion of can be increased.

[0045] The above D in requirement (A4) sol The proportion of the ethylene-derived structural units can be adjusted by adjusting the ratio of the amount of ethylene fed to the amount of propylene fed when carrying out [Step 2]. In other words, by increasing the ratio of this feed amount, the proportion of the structural units can be increased, and by decreasing the ratio of this feed amount, the proportion of the structural units can be decreased.

[0046] Intrinsic viscosity [η sol ] can be adjusted by the amount of hydrogen gas fed as a chain transfer agent in [Step 2]. In other words, the intrinsic viscosity [η sol ] can be reduced, and the intrinsic viscosity [η sol ] can be made larger.

[0047] After the polymerization is completed, known post-treatment steps such as a catalyst deactivation step, a catalyst residue removal step, and a drying step are carried out as necessary, to obtain the propylene polymer (A) as a powder. Moreover, a commercially available product may be used as the propylene polymer (A).

[0048] <Ethylene-based polymer (B)> The ethylene polymer (B), which is one of the components constituting the propylene resin composition of the present invention, is an ethylene homopolymer or a copolymer of ethylene and an α-olefin that satisfies the following requirements (B1) and (B2).

[0049] The α-olefins include α-olefins having 3 to 20 carbon atoms, and examples thereof include propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0050] [Requirement (B1)] The melt flow rate (MFR) was measured at a temperature of 190°C and a load of 2.16 kg in accordance with JIS K 7210. B ) is 1 g / 10 min or more and less than 30 g / 10 min, preferably 1 to 20 g / 10 min, and more preferably 1 to 10 g / 10 min.

[0051] If the MFR of the ethylene polymer (B) is below the above range, the impact resistance of the molded article obtained from the propylene resin composition tends to be poor. This is believed to be because poor dispersion occurs when the molecular weight is high. If it exceeds the above range, the impact resistance of the molded article obtained from the propylene resin composition tends to be poor. This is believed to be because the absorption energy against impact decreases when the molecular weight is low.

[0052] [Requirements (B2)] Density: 950-966kg / m 3 and preferably 955 to 966 kg / m 3 , more preferably 960 to 966 kg / m 3 It is.

[0053] The density value of the ethylene polymer (B) was measured by a density gradient tube method using a sample obtained by heat-treating a strand obtained during the measurement of the MFR of the ethylene polymer (B) at 120°C for 1 hour and slowly cooling it to room temperature over 1 hour. The ethylene / α-olefin copolymer (B) according to the present invention can be produced by a conventionally known method.

[0054] MFR in Requirement (B1) BThe MFR can be adjusted by adjusting the ratio of the amount of hydrogen gas fed as a chain transfer agent to the amount of ethylene or ethylene and α-olefin fed when ethylene or ethylene and α-olefin are copolymerized to produce the ethylene-based polymer (B). B By reducing this ratio, the MFR can be increased. B can be lowered.

[0055] The density in requirement (B2) can be adjusted by adjusting the ratio of the amount of α-olefin fed to the amount of ethylene fed when ethylene or ethylene and an α-olefin are copolymerized to produce the ethylene polymer (B). That is, by increasing the amount of α-olefin fed, the density can be lowered, and by decreasing the amount of α-olefin fed, the density can be increased. Commercially available products may also be used as the ethylene polymer (B), examples of which include HI-ZEX manufactured by Prime Polymer Co., Ltd. and NOVATEC manufactured by Japan Polyethylene Corporation.

[0056] <Propylene-Based Resin Composition> The propylene-based resin composition of the present invention is a composition containing 85 to 95 parts by mass, preferably 85 to 94 parts by mass, of the propylene-based polymer (A) and 5 to 15 parts by mass, preferably 6 to 15 parts by mass, of the ethylene-based polymer (B) (wherein the total amount of the propylene-based polymer (A) and the ethylene-based polymer (B) is 100 parts by mass).

[0057] If the amount of the ethylene polymer (B) is less than the above range, the effect of improving the whitening of sink marks in the molded article obtained from the propylene resin composition tends to be inferior. This is believed to be due to the fact that the effect of dispersing and absorbing the stress generated during molding shrinkage is reduced. Also, if the amount of the ethylene polymer (B) is more than the above range, the rigidity of the molded article obtained from the propylene resin composition tends to be inferior. This is believed to be due to the fact that the component of the propylene polymer (A) that contributes to rigidity is reduced.

[0058] The propylene-based resin composition of the present invention contains, in addition to the propylene-based polymer (A) and the ethylene-based polymer (B), preferably 0.03 to 0.2 parts by mass, 0.03 to 0.4 parts by mass, more preferably 0.04 to 0.25 parts by mass, and even more preferably 0.05 to 0.10 parts by mass of the following nucleating agent, relative to 100 parts by mass of the total amount of the propylene-based polymer (A) and the ethylene-based polymer (B).

[0059] [Nucleating agent (C)] The nucleating agent contained in the propylene-based resin composition of the present invention is not particularly limited, and examples thereof include sorbitol-based nucleating agents, phosphorus-based nucleating agents, metal carboxylate-based nucleating agents, polymer nucleating agents, inorganic compounds, etc. As the nucleating agent, sorbitol-based nucleating agents, phosphorus-based nucleating agents, and polymer nucleating agents are preferred.

[0060] Specific examples of sorbitol-based nucleating agents include 1,2,3-trideoxy-4,6:5,7-bis-O-[(4-propylphenyl)methylene]-nonitol (commercially available products containing this compound include the trade name "Milad NX8000" series manufactured by Milliken ("NX8000" is the above chemical substance + fluorescent brightener + blooming agent, "NX8000K" is "NX8000" without the fluorescent brightener, and "NX8000J" is without both the fluorescent brightener and the blooming agent)), 1,3,2,4-dibenzylidene sorbitol, 1,3,2,4-di-(p-methylbenzylidene) sorbitol, and 1,3-p-chlorobenzylidene-2,4-p-methylbenzylidene sorbitol.

[0061] Specific examples of phosphorus-based nucleating agents include sodium bis-(4-t-butylphenyl) phosphate, potassium bis-(4-t-butylphenyl) phosphate, sodium 2,2'-ethylidene bis(4,6-di-t-butylphenyl) phosphate, sodium 2,2'-methylene bis(4,6-di-t-butylphenyl) phosphate, and bis(2,4,8,10-tetra-t-butyl-6-hydroxy-12H-dibenzo[d,g][1,3,2]dioxaphosphocin-6-oxide) sodium salt (trade name "ADK STAB (registered trademark)"). Examples of such a composite include a composite having bis(2,4,8,10-tetra-t-butyl-6-hydroxy-12H-dibenzo[d,g][1,3,2]dioxaphosphocin-6-oxide) aluminum hydroxide salt as the main component (trade name "ADK STAB NA-21", manufactured by ADEKA Corporation), and a composite containing lithium-2,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate and 12-hydroxystearic acid and containing lithium as an essential component (trade name "ADK STAB NA-71", manufactured by ADEKA Corporation).

[0062] Specific examples of the metal carboxylate nucleating agent include aluminum pt-butylbenzoate, aluminum hydroxy-di(pt-butylbenzoate) (product name "AL-PTBBA", manufactured by Japan Chemtech), aluminum adipate, and sodium benzoate.

[0063] As the polymer nucleating agent, a branched α-olefin polymer is preferably used. Examples of the branched α-olefin polymer include homopolymers of 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene, or copolymers thereof, and further copolymers thereof with other α-olefins. In particular, a polymer of 3-methyl-1-butene is preferred from the viewpoint of low-temperature impact resistance, good rigidity properties, and economic efficiency.

[0064] Specific examples of inorganic compounds include talc, mica, and calcium carbonate. Among these nucleating agents, bis(2,4,8,10-tetra-t-butyl-6-hydroxy-12H-dibenzo[d,g][1,3,2]dioxaphosphocin-6-oxide) sodium salt, 1,2,3-trideoxy-4,6:5,7-bis-O-[(4-propyphenyl)methylene]-nonitol, and hydroxy-di(pt-butylbenzoate)aluminum are preferred.

[0065] These nucleating agents may be used alone or in combination of two or more. When the propylene-based resin composition of the present invention contains a nucleating agent (C), the composition is formed into large molded articles such as containers and pallets with excellent rigidity, which is presumably due to the high rigidity resulting from the improved crystallinity.

[0066] The propylene-based resin composition of the present invention may contain, as appropriate, components exemplified by additives such as neutralizing agents, antioxidants, heat stabilizers, weather resistance agents, lubricants, ultraviolet absorbers, antistatic agents, antiblocking agents, antifogging agents, bubble inhibitors, dispersants, flame retardants, antibacterial agents, fluorescent brightening agents, crosslinking agents, and crosslinking assistants; and colorants such as dyes and pigments (hereinafter referred to as "other components"), within the scope of the present invention.

[0067] When the propylene-based resin composition of the present invention contains other components, the amount of the other components is usually 0.01 to 5 parts by mass per 100 parts by mass of the total of the propylene-based polymer (A) and the ethylene-based polymer (B).

[0068] The propylene-based resin composition of the present invention has a melt flow rate (hereinafter, also simply referred to as "MFR") measured in accordance with JIS K 7210 at a measurement temperature of 230°C and a load of 2.16 kg of usually 1 to 30 g / 10 min, preferably 1 to 20 g / 10 min, and more preferably 1 to 15 g / 10 min.

[0069] <<Method for producing propylene-based resin composition>> The method for producing the propylene-based resin composition of the present invention is not particularly limited, but examples of the production method include a method in which each component is melt-kneaded in a kneader to produce a propylene-based resin composition. Examples of the kneader include a single-screw kneading extruder, a multi-screw kneading extruder, a kneader, a Banbury mixer, and a Henschel mixer. The melt-kneading conditions are not particularly limited as long as the molten resin is not deteriorated due to shear during kneading, heating temperature, heat generation due to shear, etc. From the viewpoint of preventing deterioration of the molten resin, it is effective to appropriately set the heating temperature or add an antioxidant or a heat stabilizer.

[0070] <Molded body> The molded article of the present invention is characterized by containing the above-mentioned propylene-based resin composition of the present invention. Specific examples thereof include those obtained by subjecting the propylene-based resin composition of the present invention to extrusion molding, compression molding, and injection molding. Among these molded articles, the injection molded article is preferred.

[0071] Examples of the molded article of the present invention include containers, home appliance parts, housing equipment, daily necessities, containers, pallets, and other logistics applications. Among these, large molded articles such as containers and pallets are preferred from the viewpoint of impact resistance and rigidity. EXAMPLES

[0072] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these. Working Example , reference example The physical properties of the polymers used in the comparative examples were measured by the following methods.

[0073] <Properties of Propylene Polymer (A)> [MFR A 〕 Melt flow rate (MFR) of propylene-based polymer pellets A ) was measured in accordance with JIS K 7210 (230°C, 2.16 kg load).

[0074] [D insol and D.sol amount〕 D of propylene polymer (A) insol and D. sol The ratio was calculated by the following method. 200 mL of n-decane is added to 5 g of a sample of the propylene polymer (A), and the mixture is heated at 145° C. for 30 minutes to dissolve, thereby obtaining a solution (1).

[0075] Next, the solution is cooled to room temperature (25° C.) over about 2 hours, and then allowed to stand at 25° C. for 30 minutes to obtain a solution (2) containing a precipitate (α). Thereafter, the precipitate (α) is separated from the solution (2) by filtration using a filter cloth having an opening of about 15 μm, and the precipitate (α) is dried and then the mass of the precipitate (α) is measured. The mass of the precipitate (α) divided by the sample mass (5 g) is determined as the n-decane insoluble portion D. insol The ratio is as follows:

[0076] Furthermore, the solution (2) from which the precipitate (α) has been filtered off is placed in acetone in an amount approximately three times the amount of the solution (2) to precipitate the components dissolved in n-decane, thereby obtaining a precipitate (β). Thereafter, the precipitate (β) is filtered off using a glass filter (G2, mesh size: approximately 100 to 160 μm) and dried, and then the mass of the precipitate (β) is measured. The mass of the precipitate (β) at this time was divided by the sample mass (5 g) to obtain the n-decane soluble fraction (D sol ) as a percentage.

[0077] [D sol The intrinsic viscosity [η sol ]〕 The propylene polymer (A) sol The intrinsic viscosity [η sol was determined as follows: The sample is the above D insol and D. sol The precipitate (β) obtained when the ratio of was calculated was used. Approximately 25 mg of this sample is dissolved in 25 mL of decalin, and the specific viscosity ηsp is measured in an oil bath at 135°C.

[0078] This decalin solution is diluted with an additional 5 mL of decalin solvent, and the specific viscosity ηsp is measured in the same manner. This dilution procedure is repeated two more times, and the value of ηsp / C when the concentration (C) is extrapolated to 0 is calculated as the limiting viscosity, and this value is called D sol The intrinsic viscosity [η sol ].

[0079] [D sol [Content of ethylene-derived skeleton in The propylene polymer (A) sol The content of ethylene-derived skeleton in 13 It was determined by measurement and calculation as follows based on the CNMR measurement. The sample is the above D insol and D. sol The precipitates (α) and (β) obtained when the ratio of was calculated were used. The precipitates (α) and (β) were used as samples and were subjected to the following conditions: 13 C-NMR measurements were performed.

[0080] < 13 C-NMR measurement conditions> Measurement equipment: JEOL LA400 type nuclear magnetic resonance spectrometer Measurement mode: BCM (Bilevel Complete decoupling) Observation frequency: 100.4MHz Observation range: 17006.8Hz Pulse width: C core 45° (7.8 μsec) Pulse repetition time: 5 seconds Sample tube: 5mmφ Sample tube rotation speed: 12Hz Accumulation count: 20,000 times Measurement temperature: 125℃ Solvent: 1,2,4-trichlorobenzene: 0.35 mL / heavy benzene: 0.2 mL Sample size: approx. 40 mg

[0081] From the spectrum obtained by the measurement, the ratio of monomer chain distribution (triad distribution) was determined according to the following literature (1), and the above-mentioned D insol and D. sol The molar fraction (mol%) of the structural unit derived from ethylene (hereinafter referred to as E (mol%)) and the molar fraction (mol%) of the structural unit derived from propylene (hereinafter referred to as P (mol%)) were calculated. The calculated E (mol%) and P (mol%) were converted to mass% according to the following (Equation 1) to obtain the D of the propylene-based polymer. insol and D. sol The content (mass%) of structural units derived from ethylene (hereinafter referred to as E (wt%)) was calculated. E(wt%)=E(mol%)×28×100 / [P(mol%)×42+E(mol%)×28] (Formula 1) Literature (1): Kakugo, M.; Naito, Y.; Mizunuma, K.; Miyatake, T., Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with delta-titanium trichloride-diethylaluminum chloride. Macromolecules 1982, 15, (4), 1150-1152

[0082] <Physical Properties of Ethylene Polymer (B)> [MFR B 〕 Melt flow rate (MFR) according to JIS K 7210 (measurement temperature 190℃, load 2.16kg) B ) was measured.

[0083] 〔density〕 The strand obtained during the melt flow rate measurement (ASTM D-1238) was heat-treated at 120°C for 1 hour and slowly cooled to room temperature over 1 hour. The resulting sample was used for density measurement by a density gradient tube method to determine the density of the ethylene polymer. Working Example and reference examplesPropylene-based polymer (A) used in And The propylene polymer (E) used in the comparative examples was a propylene polymer produced by the following production method.

[0084] [Production of Propylene-Based Polymer (A-1)] (1) Preparation of solid catalyst components 95.2 g of anhydrous magnesium chloride, 442 mL of decane, and 390.6 g of 2-ethylhexyl alcohol were reacted by heating at 130°C for 2 hours to obtain a homogeneous solution, and then 21.3 g of phthalic anhydride was added to this solution, followed by stirring and mixing at 130°C for an additional hour to dissolve the phthalic anhydride.

[0085] The homogeneous solution thus obtained was cooled to room temperature, and then 75 mL of this homogeneous solution was added dropwise over one hour to 200 mL of titanium tetrachloride kept at -20° C. After the addition was completed, the temperature of this mixture was raised to 110° C. over four hours, and when it reached 110° C., 5.22 g of diisobutyl phthalate (DIBP) was added, and the mixture was stirred and kept at the same temperature for two hours.

[0086] After the 2-hour reaction, the solid portion was collected by hot filtration, resuspended in 275 mL of titanium tetrachloride, and then heated again for 2 hours at 110° C. After the reaction was completed, the solid portion was collected again by hot filtration, and thoroughly washed with decane and hexane at 110° C. until no free titanium compounds were detected in the solution.

[0087] Here, the detection of the free titanium compounds was confirmed by the following method. 10 mL of the supernatant of the solid catalyst component was collected with a syringe and charged into a 100 mL sidearm Schlenk tube that had been previously replaced with nitrogen. Next, the solvent hexane was dried with a nitrogen stream and further vacuum dried for 30 minutes. 40 mL of ion-exchanged water and 10 mL of 50% by volume sulfuric acid were charged and stirred for 30 minutes. This aqueous solution was transferred to a 100 mL measuring flask through a filter paper, followed by the addition of 1 mL of conc. H3PO4 as a masking agent for iron (II) ions and 5 mL of 3% H2O2 aqueous solution as a titanium coloring reagent, and then the volume was increased to 100 mL with ion-exchanged water. The measuring flask was shaken, and after 20 minutes, the absorbance at 420 nm was observed using UV to detect free titanium. Washing removal of free titanium and detection of free titanium were continued until this absorption was no longer observed.

[0088] The solid titanium catalyst component (A) prepared as above was stored as a decane slurry, and a part of it was dried for the purpose of examining the catalyst composition. The composition of the solid titanium catalyst component (A) thus obtained was 2.3 mass% titanium, 61 mass% chlorine, 19 mass% magnesium, and 12.5 mass% DIBP.

[0089] (2) Preparation of prepolymerized catalyst component After replacing the inside of a 500mL three-necked flask equipped with a stirrer with nitrogen gas, 400mL of dehydrated heptane, 19.2mmol of triethylaluminum, 3.8mmol of dicyclopentyldimethoxysilane, and 4g of the above solid titanium catalyst component (A) were added. The internal temperature was kept at 20°C, and propylene was introduced while stirring. After 1 hour, the stirring was stopped, and as a result, a prepolymerized catalyst component (B) was obtained in which 2g of propylene was polymerized per 1g of the solid titanium catalyst component (A).

[0090] (3-1) Polymerization-1 (Polymerization [Step 1]) A 10L stainless steel autoclave equipped with a stirrer was thoroughly dried and purged with nitrogen, after which 6L of dehydrated heptane, 12.5mmol of triethylaluminum, and 0.6mmol of dicyclopentyldimethoxysilane were added. After the nitrogen in the system was substituted with propylene, hydrogen was charged at 0.17MPa-G. After the system was stabilized at an internal temperature of 80°C and a total pressure of 3.2 MPa-G, 20.8 mL of a heptane slurry containing 0.10 mmol of the prepolymerized catalyst component (B) in terms of Ti atom was added, and polymerization was carried out at 80°C for 1 hour while continuously supplying propylene.

[0091] (3-2) Polymerization-2 (Polymerization [Step 2]) After the polymerization of propylene homopolymer was completed (after the above [Step 1]), the internal temperature was lowered to 30°C and the pressure was released. Then, hydrogen / ethylene = 0.10mr was charged, followed by the introduction of a mixed gas of ethylene / (ethylene + propylene) = 0.40mr. Propylene / ethylene copolymerization was carried out for 50 minutes at an internal temperature of 60°C and a total pressure of 0.60MPa-G (varies depending on the amount of gas introduced).

[0092] After the specified time had elapsed, 50 mL of methanol was added to stop the reaction, and the temperature and pressure were lowered. The entire content was transferred to a filtration tank equipped with a filter and heated to 60°C for solid-liquid separation. The solid portion was then washed twice with 6 L of heptane at 60°C. The propylene-ethylene copolymer thus obtained was vacuum dried.

[0093] The melt flow rate (MFR) (JIS K 7210, measurement temperature 230°C, load 2.16 kg) of the obtained propylene polymer (A-1) was 5.0 g / 10 min., D insol is 88.0 mass%, D sol is 12.0 mass%, and the intrinsic viscosity [η sol ] is 3.3dL / g, D sol The mass of the structural units derived from ethylene therein was 33.0 mass%.

[0094] [Production of Propylene Polymer (A-2)] The steps (1) and (2) are the same as those for the propylene polymer (A-1). (3-1) Polymerization-1 (Polymerization [Step 1]) A 10L stainless steel autoclave equipped with a stirrer was thoroughly dried and purged with nitrogen, after which 6L of dehydrated heptane, 12.5mmol of triethylaluminum, and 0.6mmol of dicyclopentyldimethoxysilane were added. After the nitrogen in the system was substituted with propylene, hydrogen was charged at 0.35MPa-G. After the system was stabilized at an internal temperature of 80°C and a total pressure of 3.2 MPa-G, 20.8 mL of a heptane slurry containing 0.10 mmol of the prepolymerized catalyst component (B) in terms of Ti atom was added, and polymerization was carried out at 80°C for 1 hour while continuously supplying propylene.

[0095] (3-2) Polymerization-2 (Polymerization [Step 2]) After the polymerization of propylene homopolymer was completed (after the above [Step 1]), the internal temperature was lowered to 30°C and the pressure was released. Then, hydrogen / ethylene = 0.10mr was charged, followed by the introduction of a mixed gas of ethylene / (ethylene + propylene) = 0.40mr. Propylene / ethylene copolymerization was carried out for 50 minutes at an internal temperature of 60°C and a total pressure of 0.60MPa-G (varies depending on the amount of gas introduced).

[0096] After the specified time had elapsed, 50 mL of methanol was added to stop the reaction, and the temperature and pressure were lowered. The entire content was transferred to a filtration tank equipped with a filter and heated to 60°C for solid-liquid separation. The solid portion was then washed twice with 6 L of heptane at 60°C. The propylene-ethylene copolymer thus obtained was vacuum dried.

[0097] The melt flow rate (MFR) (JIS K 7210, measurement temperature 230°C, load 2.16 kg) of the obtained propylene polymer (A-2) was 10 g / 10 min, D insol is 88.0 mass%, D sol is 12.0 mass%, and the intrinsic viscosity [η sol ] is 3.4 dL / g, D sol The mass of the structural units derived from ethylene therein was 33.0 mass%.

[0098] [Production of Propylene Polymer (E-1)] The steps (1) and (2) are the same as those for the propylene polymer (A-1). (3-1) Polymerization-1 (Polymerization [Step 1]) A 10L stainless steel autoclave equipped with a stirrer was thoroughly dried and purged with nitrogen, after which 6L of dehydrated heptane, 12.5mmol of triethylaluminum, and 0.6mmol of dicyclopentyldimethoxysilane were added. After the nitrogen in the system was substituted with propylene, hydrogen was charged at 0.15MPa-G. After the system was stabilized at an internal temperature of 80°C and a total pressure of 3.2 MPa-G, 20.8 mL of a heptane slurry containing 0.10 mmol of the prepolymerized catalyst component (B) in terms of Ti atom was added, and polymerization was carried out at 80°C for 1 hour while continuously supplying propylene.

[0099] (3-2) Polymerization-2 (Polymerization [Step 2]) After the polymerization of propylene homopolymer was completed (after the above [Step 1]), the internal temperature was lowered to 30°C and the pressure was released. Then, hydrogen / ethylene = 0.20mr was charged, followed by the introduction of a mixed gas of ethylene / (ethylene + propylene) = 0.40mr. Propylene / ethylene copolymerization was carried out for 50 minutes at an internal temperature of 60°C and a total pressure of 0.60MPa-G (varies depending on the amount of gas introduced).

[0100] After the specified time had elapsed, 50 mL of methanol was added to stop the reaction, and the temperature and pressure were lowered. The entire content was transferred to a filtration tank equipped with a filter and heated to 60°C for solid-liquid separation. The solid portion was then washed twice with 6 L of heptane at 60°C. The propylene-ethylene copolymer thus obtained was vacuum dried.

[0101] The melt flow rate (MFR) (JIS K 7210, measurement temperature 230°C, load 2.16 kg) of the obtained propylene polymer (E-1) was 5.0 g / 10 min, D insol is 88.0 mass%, D sol is 12.0 mass%, and the intrinsic viscosity [η sol ] is 2.0 dL / g, D sol The mass of the structural units derived from ethylene therein was 33.0 mass%.

[0102] [Production of Propylene Polymer (E-2)] The steps (1) and (2) are the same as those for the propylene polymer (A-1). (3-1) Polymerization-1 (Polymerization [Step 1]) A 10L stainless steel autoclave equipped with a stirrer was thoroughly dried and purged with nitrogen, after which 6L of dehydrated heptane, 12.5mmol of triethylaluminum, and 0.6mmol of dicyclopentyldimethoxysilane were added. After the nitrogen in the system was substituted with propylene, hydrogen was charged at 0.17MPa-G. After the system was stabilized at an internal temperature of 80°C and a total pressure of 3.2 MPa-G, 20.8 mL of a heptane slurry containing 0.10 mmol of the prepolymerized catalyst component (B) in terms of Ti atom was added, and polymerization was carried out at 80°C for 1 hour while continuously supplying propylene.

[0103] (3-2) Polymerization-2 (Polymerization [Step 2]) After the polymerization of propylene homopolymer was completed (after the above [Step 1]), the internal temperature was lowered to 30°C and the pressure was released. Then, hydrogen / ethylene = 0.10 ml was charged, followed by the introduction of a mixed gas of ethylene / (ethylene + propylene) = 0.21 ml. Propylene / ethylene copolymerization was carried out for 50 minutes at an internal temperature of 60°C and a total pressure of 0.60 MPa-G (varies depending on the amount of gas introduced).

[0104] After the specified time had elapsed, 50 mL of methanol was added to stop the reaction, and the temperature and pressure were lowered. The entire content was transferred to a filtration tank equipped with a filter and heated to 60°C for solid-liquid separation. The solid portion was then washed twice with 6 L of heptane at 60°C. The propylene-ethylene copolymer thus obtained was vacuum dried.

[0105] The melt flow rate (MFR) (JIS K 7210, measurement temperature 230°C, load 2.16 kg) of the obtained propylene polymer (E-2) was 5.0 g / 10 min., D insol is 88.0 mass%, D sol is 12.0 mass%, and the intrinsic viscosity [η sol ] is 3.3dL / g, D sol The mass of the structural units derived from ethylene was 22.0 mass%.

[0106] [Production of Propylene Polymer (E-3)] The steps (1) and (2) are the same as those for the propylene polymer (A-1). (3-1) Polymerization-1 (Polymerization [Step 1]) A 10L stainless steel autoclave equipped with a stirrer was thoroughly dried and purged with nitrogen, after which 6L of dehydrated heptane, 12.5mmol of triethylaluminum, and 0.6mmol of dicyclopentyldimethoxysilane were added. After the nitrogen in the system was substituted with propylene, hydrogen was charged at 0.25MPa-G. After the system was stabilized at an internal temperature of 80°C and a total pressure of 3.2 MPa-G, 20.8 mL of a heptane slurry containing 0.10 mmol of the prepolymerized catalyst component (B) in terms of Ti atom was added, and polymerization was carried out at 80°C for 1 hour while continuously supplying propylene.

[0107] (3-2) Polymerization-2 (Polymerization [Step 2]) After the polymerization of propylene homopolymer was completed (after the above [Step 1]), the internal temperature was lowered to 30°C and the pressure was released. Then, hydrogen / ethylene = 0.04mr was charged, followed by the introduction of a mixed gas of ethylene / (ethylene + propylene) = 0.33mr. Propylene / ethylene copolymerization was carried out for 70 minutes at an internal temperature of 60°C and a total pressure of 0.60MPa-G (varies depending on the amount of gas introduced).

[0108] After the specified time had elapsed, 50 mL of methanol was added to stop the reaction, and the temperature and pressure were lowered. The entire content was transferred to a filtration tank equipped with a filter and heated to 60°C for solid-liquid separation. The solid portion was then washed twice with 6 L of heptane at 60°C. The propylene-ethylene copolymer thus obtained was vacuum dried.

[0109] The melt flow rate (MFR) (JIS K 7210, measurement temperature 230°C, load 2.16 kg) of the obtained propylene polymer (E-3) was 5.0 g / 10 min, D insol is 85.0 mass%, D sol is 15.0 mass%, and the intrinsic viscosity [η sol ] is 4.5dL / g, D solThe mass of the structural units derived from ethylene was 29.0 mass%.

[0110] Working Example , reference example The ethylene polymers used in the comparative examples are shown below. [Ethylene-based polymer (B-1)] Density 964kg / m 3 , MFR (190℃) 5.2g / 10min (Prime Polymer, product name: Hi-Zex: 2200J) [Ethylene-based polymer ( F -1) Density 90 3 kg / m 3 , MFR (190℃) 3.8g / 10min (Prime Polymer, product name EVOLUE: SP0540)

[0111] Working Example , reference example The propylene-based resin compositions used in the comparative examples were prepared in the following manner. (1) Granulation Table 1 (Example ·Reference example In the formulation shown in (Comparative Example), a propylene-based polymer and an ethylene-based polymer were blended in predetermined amounts, and as additives, 0.05 parts by mass of a phenol-based antioxidant Irganox1010 (product name, manufactured by BASF), 0.05 parts by mass of a phosphorus-based antioxidant Irgafos168 (product name, manufactured by BASF), 0.10 parts by mass of a neutralizing agent calcium stearate (manufactured by Nitto Kasei), and 0.10 parts by mass of an AL-PTBBA (product name, manufactured by DIC) as a nucleating agent were blended and stirred and mixed in a Henschel mixer.

[0112] The resulting mixture was melt-kneaded under the following conditions using a twin-screw extruder (TEM35BS) manufactured by Toshiba Machine Co., Ltd. to obtain a strand-like propylene-based resin composition. Model: TEM35BS (35mm twin screw extruder) Screw rotation speed: 300 rpm Discharge amount: 30kg / h Screen mesh: #200 Resin temperature: 230℃

[0113] The resulting strand was cooled with water and then cut with a pelletizer to obtain pellets of the propylene-based resin composition. Working Example , reference example The molded articles obtained in the comparative examples were evaluated by the following methods.

[0114] [Sink mark whitening evaluation] The pellets of the propylene-based resin composition were used to mold a container by the following method.

[0115] Using an electric injection molding machine (NEX140 IV-18E manufactured by Nissei Plastic Industrial Co., Ltd.) with a clamping force of 140 tons, pellets of the propylene-based resin composition were injection molded under the conditions of a cylinder temperature of 230°C, a mold temperature of 20°C, a primary injection pressure of 100 MPa, an injection speed of 30 mm / sec, an injection filling time of 2.5 sec, a holding pressure of 55 MPa, a holding time of 12.5 sec, and a cooling time of 60 sec, to obtain the molded product shown in FIG. 1.

[0116] The whitening of sink marks on the back side of the rib shape was visually evaluated and judged on a 5-level scale as shown below. 1: Whitening is very noticeable 2: Whitening is noticeable 3: Whitening is somewhat noticeable 4: Whitening is barely noticeable 5: Not bleached

[0117] [Tensile modulus] Test pieces were molded by injection molding, and after molding, they were left to stand for 72 hours in a constant temperature room adjusted to a room temperature of 23±5°C and a relative humidity of 50±5%, and then the properties were measured in accordance with JIS K 7161.

[0118] [Charpy impact strength (notched, 23°C)] Test pieces were molded by injection molding, and after molding, they were left to stand for 72 hours in a constant temperature room adjusted to a room temperature of 23±5°C and a relative humidity of 50±5%, and then the hardness was measured in accordance with JIS K 7111.

[0119] [ reference Example 1 94 parts by mass of the propylene-based polymer (A-1) obtained by the above-mentioned production method and 6 parts by mass of the ethylene-based polymer (B-1) were blended and granulated by the above-mentioned method to obtain a propylene-based resin composition. Then, a molded body and a test piece were prepared by the above-mentioned method, and the physical properties were measured by the above-mentioned method. The results are shown in Table 1.

[0120] [Examples 2 and 3] reference The propylene-based resin composition used in Example 1 was replaced with the propylene-based polymer (A-1) and the ethylene-based polymer (B-1) in the amounts shown in Table 1. reference The same procedure as in Example 1 was carried out to prepare molded bodies and test pieces, and the physical properties were measured by the methods described above. The results are shown in Table 1.

[0121] Example 4 The procedure of Example 2 was repeated except that the propylene polymer (A-2) was used instead of the propylene polymer (A-1) used in Example 2, to prepare molded articles and test pieces, and the physical properties were measured by the methods described above. The results are shown in Table 1.

[0122] Comparative Example 1 reference Except for using the propylene-based polymer (A-1) alone instead of the propylene-based resin composition used in Example 1, reference The same procedure as in Example 1 was carried out to prepare molded bodies and test pieces, and the physical properties were measured by the methods described above. The results are shown in Table 1.

[0123] [Comparative Examples 2 to 6] reference The propylene-based resin composition used in Example 1 was replaced with the propylene-based polymer and ethylene-based polymer shown in Table 1, and the blending amounts thereof were the same as those shown in Table 1. reference The same procedure as in Example 1 was carried out to prepare molded bodies and test pieces, and the physical properties were measured by the methods described above. The results are shown in Table 1.

[0124] [Table 1]

Claims

1. A propylene-based resin composition comprising 85 to 90 parts by mass of a propylene-based polymer (A) satisfying the following requirements (A1) to (A5), and 10 to 15 parts by mass of an ethylene-based polymer (B) satisfying the following requirements (B1) and (B2) (wherein the total amount of the propylene-based polymer (A) and the ethylene-based polymer (B) is 100 parts by mass). (A1) Melt flow rate (MFR) measured at a measurement temperature of 230° C. and a load of 2.16 kg in accordance with JIS K 7210 A ) is 1 to 30 g / 10 min. (A2) It contains a propylene homopolymer segment obtained by polymerizing propylene alone, and a propylene-ethylene copolymer segment obtained by copolymerizing propylene and ethylene. (A3) Part insoluble in n-decane at room temperature (D insol ) in an amount of 86 to 95% by mass, and a portion soluble in n-decane at room temperature (D sol ) in an amount of 5 to 14 mass % [wherein (D insol ) and (D sol ) is 100 mass % in total. (A4) Part soluble in n-decane at room temperature (D sol ) has a content of structural units derived from ethylene of 25% by mass or more and less than 45% by mass. (A5) A portion soluble in n-decane at room temperature (D sol ) has an intrinsic viscosity [η] of 2.5 to 4.0 dL / g in decalin at 135°C. (B1) Melt flow rate (MFR) measured in accordance with JIS K 7210 at a measurement temperature of 190° C. and a load of 2.16 kg B ) is 1 g / 10 min or more and less than 30 g / 10 min. (B2) Density is 950 to 966 kg / m 3 It is.

2. 2. The propylene-based resin composition according to claim 1, further comprising a nucleating agent in an amount of 0.03 to 0.2 parts by mass per 100 parts by mass of the propylene-based resin composition.

3. A molded article obtained by injection molding the propylene-based resin composition according to claim 1 or 2.

4. The molded article according to claim 3 , which has a rib shape.

5. 5. The molded article according to claim 3, which is a container or a pallet.

Citation Information

Patent Citations

  • Propylene resin composition

    JP1988090552A

  • Propylene resin composition and use of the same

    JP2004182955A

  • Propylene resin composition and its molded article

    JP2008255319A

  • Propylene-based resin composition and molded body obtained therefrom

    JP2011184620A

  • Talc-containing polypropylene resin composition

    JP2016084386A